Case report: anomalous left coronary artery from the pulmonary artery (Bland-White-Garland syndrome) in an adult patient - N. A. Androsov; N. S. Shamrina; A. A. Shiryaev; A. V. Shirkin; Yu. G. Matchin (Евразийский Кардиологический Журнал)
A rare clinical case of malformation of the coronary arteries is considered – anomalous left coronary artery from the pulmonary artery (Bland-WhiteGarland syndrome) in a 61-year-old patient. Detailed visualization in the form of angiograms and multispiral-CT, including those after surgery, is presented.